Does mobile financial services adoption mitigate financial ?vulnerability of small enterprises? - Jesse ERIOLA (Academic Finance, 2025)
Purpose: This study investigates the impact of mobile financial services (MFS) adoption on the financial vulnerability of small businesses in Benin, with a focus on the moderating role of government support.